Recent Progress on Metal–Organic Framework and Its Derivatives as Novel Fire Retardants to Polymeric Materials - Zhang, Jing; Li, Zhi; Qi, Xiao‑Lin; Wang, De‑Yi (Nano-Micro Letters, 2020)
High flammability of polymers has become a major issue which has restricted its applications. Recently, highly crystalline materials and metal–organic frameworks (MOFs), which consisted of metal ions and organic linkers, have been intensively employed as novel fire retardants (FRs) for a variety of polymers (MOF/polymer). The MOFs possessed abundant transition metal species, fire-retardant elements and potential carbon source accompanied with the facile tuning of the structure and property, making MOF, its derivatives and MOF hybrids promising for fire retardancy research. The recent progress and strategies to prepare MOF-based FRs are emphasized and summarized. The fire retardancy mechanisms of MOF/polymer composites are explained, which may guide the future design for efficient MOF-based FRs. Finally, the challenges and prospects related to different MOF-based FRs are also discussed and aim to provide a fast and holistic overview, which is beneficial for researchers to quickly get up to speed with the latest development in this field. Highlights: 1 Recent advances of metal–organic frameworks (MOFs) in the fire-retardant polymeric materials are reviewed. 2 State of the art to the novel strategies for functionalizing MOFs as fire retardants is critically and comprehensively discussed.